Extremist Movements’ Manipulation Of Hadith Texts: A Critical Analysis Of Interpretive Distortions (The Journal of Interdisciplinary Human Studies, 2026)
This article critically examines the methods through which historical and contemporary extremist movements have manipulated hadith texts to support radical ideological positions. The study analyzes three principal categories of interpretive distortion: the Kharijite and Shiite approaches to selective hadith utilization, the contradictions inherent in sectarian movements’ hadith interpretation, and the pseudo- Salafi appropriation of prophetic traditions for extremist purposes. Drawing on primary Arabic sources and the critiques of mainstream Sunni scholarship (Ahl al-Sunna wa-l- Jama’a), the analysis identifies six recurring manipulative strategies: literalist surface reading (zahirism), reliance on abrogated narrations, deriving absolute rulings from singular hadiths, decontextualization, rejection of scholarly consensus, and fabrication of supportive narrations. The findings demonstrate that extremist manipulation of hadiths follows identifiable patterns that can be systematically exposed through the application of established hadith sciences, and that education in these sciences constitutes a critical preventive measure against radicalization.
Keywords: hadith manipulation; extremism; Kharijites; pseudo-Salafism; interpretive distortion; radicalization; Islamic scholarship; Ahl al-Sunna